PEMANFAATAN SOSIAL MEDIA SEBAGAI SARANA DIGITAL MARKETING PADA USAHA MIKRO KECIL MENENGAH (UMKM) - S. Anwar; A. Mawarti; T. Setiawati; S. Natalia; C. Nurhayati (Bajang Institute, 2022)
The benefits of information and communication technology have many positive impacts. However, if we are not aware of and comply with the regulations in using all the facilities and the ease of accesing the information itself, I t often causes various thing that can be detrimental. As for utilization of information technology and social media communication as a means of digital marketing for SMEs in Pagelaran Village, Ciomas District, Bogor Regency. The marketing of the product itself is still by direct marketing of offers between friends, from person to person, so that it has an impact on monotonous sales and not too many people or the surrounding community know about it. Word of mouth media makes these SMEs not yet developed. With the use of social media as a means of digital marketing, it is expected to increase sales and competitiveness in the wider market. The solution offered is to create social media, provide understanding, then proceed to mentoring, namely counseling and training on the use of social media which includes ad design and uploading advertising content on social media.